Design of Metal-Organic Polymers MIL-53(M3+): Preparation and Characterization of MIL-53(Fe) and Graphene Oxide Composite - Quang K. Nguyen (MDPI AG, 2021)
This article presents a crystal chemical analysis, generalization, and systematization of structural characteristics of metal-organic polymers MIL-53(M3+) with M = Al, Cr, Ga, and Fe. The division of the MIL-53(M3+) structures into a morphotropic series was performed, which made it possible to predict the formation of new compounds or solid solutions with the corresponding composition and structure. The change in the symmetry of MIL-53(M3+) and the causes of polymorphs formation are explained on the basis of crystal chemical rules. The efficiency of the revealed regularities in the structural characteristics of the MIL-53(M3+) phases were experimentally confirmed for MIL-53(Fe) and composite MIL-53(Fe)/GO (GO-graphene oxide) by several methods (powder X-ray, X-ray absorption, and photoelectron spectroscopy). For the first time, different coordination numbers (CN) (CNFe = 4.9 for MIL-53(Fe)—two types of coordination polyhedra with CNFe = 6 and CNFe = 4; CNFe = 4 for MIL-53 (Fe3+)/GO) and the formal charges (FC) of iron ions (variable FC of Fe (2+δ)+ in MIL-53(Fe3+) and Fe2+ in MIL-53(Fe3+)/GO) were found. These experimental data explain the higher photocatalytic activity of MIL-53(Fe3+)/GO in photo-Fenton reactions—RR195 decomposition.